Predictors of Parents' Willingness to Vaccinate Their Children Against COVID-19 in India: A Web-Based Cross-Sectional Survey - Narayana Goruntla; M Umaira Ayisha; Manjunath Sreeram (SAGE Publishing, 2023)
Background Parents are more concerned about the available evidence of the safety, efficacy, and tolerability of the pediatric COVID-19 vaccine. Aim To assess the parents' willingness to vaccinate their children against COVID-19 and associate it with health belief model constructs. Materials and Methods A countrywide, online, self-administered, cross-sectional survey was conducted from December 15, 2021 to March 8, 2022. The HBM approach was used as a theoretical context to assess the predictors of parents' willingness to vaccinate their children against COVID-19. Results The majority (1,563; 95.4%) of parents are intended to immunize their children against COVID-19. Parent education, financial status, job, number of children, age-related vaccination status of the child, and household suffering from chronic disorders were significantly associated with a parent's willingness to recommend the COVID-19 vaccine for their children. The findings of HBM constructs indicated that perceived benefits (OR 14.222; 95% CI 7.192-28.124) of the COVID-19 vaccine in children, susceptibility (OR 7.758; 95% CI 3.508-17.155) of children toward COVID-19, and severity (OR 3.820; 95% CI 2.092-6.977) of COVID-19 infection in children were significantly associated with parent acceptance to vaccinate their children. Parents' higher perception of barriers (OR 0.609; 95% CI 0.372-0.999) to vaccination reduces the intention to vaccinate children against COVID-19. Conclusion The findings of our study reveal that the value of HBM constructs in the identification of predictors associated with the parents' willingness to encourage COVID-19 vaccine for their children. It is important to improve health and reduce the barriers to COVID-19 vaccination among Indian parents having children less than 18 years.